SPL8 and miR156‐targeted SPL genes redundantly regulate Arabidopsis gynoecium differential patterning. (22nd May 2013) - Xing, Shuping; Salinas, María; Garcia‐Molina, Antoni; Höhmann, Susanne; Berndtgen, Rita; Huijser, Peter
Summary SPL8 and miR156‐targeted SPL genes are known to play an essential role in Arabidopsis anther development. Here we show that these SPL genes are also expressed within the developing gynoecium, where they redundantly control development of the female reproductive tract. Whereas the gynoecium morphology in the spl8 single mutant is largely normal, additional down‐regulation of miR156‐targeted SPL genes results in a shortened style and an apically swollen ovary narrowing onto an elongated gynophore. In particular, the septum does not form properly and lacks a transmitting tract. Loss of SPL8 function enhances the mutant phenotypes of ett, crc and spt, indicating a functional overlap between SPL8 and these genes in regulating gynoecium development. Furthermore, gynoecium development of 35S:MIR156b spl8–1 double mutants shows enhanced sensitivity to a polar auxin transport inhibitor, and the expression pattern of the auxin biosynthesis gene YUCCA4 is altered compared to wild‐type. Our observations imply that SPL8 and miR156‐targeted SPL genes control gynoecium patterning through interference with auxin homeostasis and signalling.